Analysis of results European Swimming Championship in London 2016 - Całka, Tomasz; Muszkieta, Radosław; Cieślicka, Mirosława (Journal of Education, Health and Sport, 2016)
The aim of this study is to assess the level of sports men and women swimming freestyle and butterfly at the European Championships in London in 2016. The study used the results of the European Championship, which took place in London in 2016. The event was played on a large 50-meter pool. Used materials from www.len.eu.The most balanced level of women presented at the 200 meters dolphin. The distance of 100 meters in men is more even temporarily, where women come see a big difference over time.